Lord of Shadows - Clare, Cassandra (New York: Margaret K. McElderry Books, 2017)
"Emma Carstairs has finally avenged her parents. She thought she'd be at peace. But she is anything but calm. Torn between her desire for her parabatai Julian and her desire to protect him
Keywords: Young adult fiction